Impact of a variable number tandem repeat in the CYP2C9 promoter on warfarin sensitivity and responsiveness in Jordanians with cardiovascular disease - AL-Eitan LN; Almasri AY; Al-Habahbeh SO (Dove Medical Press, 2019)
Laith N AL-Eitan,1,2 Ayah Y Almasri,1 Sahar O Al-Habahbeh1 1Department of Applied Biological Sciences, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Biotechnology and Genetic Engineering, Jordan University of Science and Technology, Irbid 22110, Jordan Purpose: The purpose of this study was to investigate the influence of CYP/CYP450 2C9 (CYP2C9) promoter variable number tandem repeat (p-VNTR) polymorphism on susceptibility to cardiovascular disease and on warfarin sensitivity and responsiveness, in Jordanians with cardiovascular disease during initiation and stabilization phases of therapy. Patients and methods: A total of 211 cardiovascular patients who were being treated with warfarin anticoagulants and 205 healthy individuals were enrolled in this study. PCR-based methods were performed to analyze the effects of CYP2C9 p-VNTR polymorphism on warfarin metabolism. The p-VNTR polymorphism was composed of tandem repeat motifs sorted into three alleles based on the length and structure: short (p-VNTR-S), middle (p-VNTR-M), and long (p-VNTR-L). Results: We found that the genotypic and allelic frequencies differ significantly between patients and healthy individuals; therefore, our results suggest that this polymorphism is associated with cardiovascular disease in the Jordanian population. Moreover, during the initiation phase of therapy, 20% of warfarin-sensitive patients were homozygous for a short allele (p-VNTR-S), and 12.2% were heterozygous for this allele (p-VNTR-M/p-VNTR-S). During the stabilization phase, no significant differences were found between these groups and their genotypic frequencies. Additionally, we did not confirm any relationship between the CYP2C9 p-VNTR polymorphism and warfarin response during either the initiation or the stabilization phases of therapy. Conclusion: Our data show a significant difference between the CYP2C9 p-VNTR polymorphism and risk of cardiovascular disease, in addition to significant association between this polymorphism and sensitivity to warfarin at the initiation phase of therapy in a Jordanian population. However, there is no correlation between this polymorphism and warfarin response, international normalized ratio (INR) values, or required warfarin dose to achieve a target INR either at the initiation or stabilization phases of therapy. To further corroborate our results, additional studies are required with a larger number of samples and different ethnic groups. Keywords: warfarin, CYP2C9 promoter variable tandem repeat, polymorphism, cardiovascular disorder, oral anticoagulant, INR, warfarin dosage